(untitled) (GAIMS Journal of Medical Sciences, 2025)
Soft tissue sarcoma is an uncommon and highly heterogeneous group of malignant tumors. The annual incidence of soft tissue sarcoma is about 50 cases per 1 million people, i.e., 1% of all malignant tumors. The field of soft tissue tumors (STT) is extremely vast; the pattern of tumors is varied, both on benign tumors and on malignant soft tissue tumors. Therefore, it is a very challenging job for a pathologist to give a final diagnosis. Here we have discussed three rare cases of soft tissue tumors.